Criptolavagem e metaverso: exame dogmático e atuação regulatória estatal - Souza, Hioman Imperiano de (2024)
The thesis has as its object the dogmatic examination of digital money laundering (crypto-laundering) and the structure of the metaverse as an environment of criminal activity. In this context, the hypotheses were organized in the respective chapters, where, first, a gradual understanding of how the criminalization of the practice of money laundering occurred, based on international aspirations. Then, the main aspects of the Vienna Convention on Trafficking and Narcotic Substances, the Declaration of Principles of the Basel Committee and the United Nations Convention against Transnational Organized Crime are demonstrated as structuring bases of the understanding about the money laundering process. capitals, going through the internalization of anti-laundering legislation in other territories, until recognition on Brazilian soil, especially from Federal Law No. 9,613, of March 3, 1998 and its subsequent update. An overview of technological advances for the analysis of the metaverse continues, considering a new environment of human coexistence in the hyperdigital world, with the list of attributes, fundamentals and intersectoral reflections in the various spheres of society, notably in the legal field. From this point on, it is examined how digital money laundering, called crypto-laundering, operates in the metaverse environment and in the use of the virtual plane, as a model of macroeconomic cybercrime, comparing it with the traditional typology of laundering, tracing dogmatic specificities of this criminal activity. Finally, state tools responsible for tackling digital money laundering are exposed, through the cooperative action of international organizations and Brazilian institutions. As a problem, the question arises about the possibility of expanding the concept of current assets to cover digital currency for the purpose of classifying it as an object of the crime of money laundering. The justification for carrying out this study is initially due to the novelty on the subject, given that the use of cryptocurrencies for laundering occurs through complex mechanisms brought about by technological innovations and, notably, because there is still a certain legislative scarcity for the regulation of both the metaverse environment and the conducts that imply digital money laundering. Therefore, based on the problem presented, the general objective is to analyze the dogmatic content of crypto-laundering, drawing a parallel with the hyperdigital environment of the metaverse and the way in which the State can act in these two scenarios, whether to face this type of laundering of money, or in the regulatory interference provided by the new super-virtual reality technologies. Methodologically, through qualitative research from a legal perspective, in the course of the investigation bibliographic and documental data collection techniques were handled, through books and scientific articles prepared by specialized authors, in addition to of relevant legislation. It can be seen that there is a real need to improve the Brazilian legal system, due to the way in which money laundering now also uses digital financial assets, which can be seen as new objects of this criminal practice (thus expanding the formal concept of currency) precisely because of the unique aspects of this practice and, likewise, to make with which the State can act with its prosecution and judicial bodies, in addition to inspection entities, within the digital world of the metaverse, notably because it is a much more conducive environment for criminals to act, where technological facilities are largely instrumentalized as tools for achieving crimes that are difficult to trace.